Globalization for Development : Trade, Finance, Aid, Migration, and Policy - Goldin, Ian; Reinert, Kenneth (Washington, DC: World Bank and Palgrave Macmillan, 2012)
Globalization and its relation to poverty reduction and development are not well understood. The book identifies the ways in which globalization can overcome poverty or make it worse. The book defines the big historical trends, identifies main global flows-trade, finance, aid, migration, and ideas-and examines how each can contribute to undermine economic development. By considering what helps and what does not, the book presents policy recommendations to make globalization more effective as a vehicle for shared growth and prosperity.